Discrepant diversity patterns and function of bacterial and fungal communities on an earthquake-prone mountain gradient in Northwest Sichuan, China - Huang, Tianzhi; Wang, Yingyan; Wang, Xuemei; Ma, Li; Yang, Xueting (Frontiers in Microbiology, 2023)
Patterns of microbial diversity on elevational gradients have been extensively studied, but little is known about those patterns during the restoration of earthquake-fractured alpine ecosystems. In this study, soil properties, soil enzyme activities, abundance and diversity of soil bacterial and fungal communities at four positions along a 2.6-km elevational gradient in the Snow Treasure Summit National Nature Reserve, located in Pingwu County, Southwest China. Although there were no significant changes in the soil chemical environment, bacterial and fungal communities were significantly different at different elevations. The overall fungal community presented an N-shaped diversity pattern with increasing elevation, while bacterial diversity decreased significantly with elevation. Changes in microbial diversity were associated with soil phosphorus, plant litter, and variations in dominant microbial taxa. Differences in enzyme activities among elevations were regulated by microbial communities, with changes in catalase and acid phosphatase activities mainly controlled by Acidobacteria and Planctomycetaceae bacteria, respectively, (catalase: P < 0.001; acid phosphatase: P < 0.01), and those in β-glucosidase, sucrase, and urease activities mainly controlled by fungi. The β-glucosidase and sucrase were both positively correlated with Herpotrichiellaceae, and urease was positively correlated with Sebacinaceae (P < 0.05). These findings contribute to the conservation and management of mountain ecosystems in the face of changing environmental conditions. Further research can delve into the specific interactions between microbial communities, soil properties, and vegetation to gain deeper insights into the intricate ecological dynamics within earthquake-prone mountain ecosystems.